Human Attrition in Information Technology (IT) - Yasmin, K.; Mazhar R, Abdul (Nepalese Journal of Management Science and Research, 2026)
IT sector is a highly paid sector when it comes to paying its employees.  Attrition should not happen in this industry.  But it happens and there are reasons for its happening.  If only the reasons are properly identified and attended to, it can be reduced.  Profits can be increased and this will pave the way for the continuous successful running of the IT sector based organizations. This study identifies that attrition is influenced by demographic variables, workplace conditions, and organizational practices. Findings reveal moderate employee satisfaction with benefits and relationships, but highlight concerns regarding promotions and overall satisfaction. Job satisfaction emerges as a key mediating factor between organizational factors and employee attrition. The study concludes that improving career growth opportunities, transparency, and work-life balance can effectively reduce attrition and enhance employee retention in IT organizations